Spinoza, the transindividual - Balibar, Étienne, 1942- (Incitements., 2020)
Étienne Balibar, one of the foremost living French philosophers, builds on his landmark work 'Spinoza and Politics' with this exploration of Spinoza's ontology. Balibar situates Spinoza in relation to the major figures of Marx and Freud as a precursor to the more recent French thinker Gilbert Simondon's concept of the transindividual.